PENGGUNAAN MEDIA CERITA BERGAMBAR UNTUK MENINGKATKAN PEMAHAMAN PENDIDIKAN SEKSUAL AWAL PADA ANAK USIA DINI DI KELOMPOK BERMAIN (KOBER) AR RAHMAH TASIKMALAYA - Rifa Nurulfatia; Ela Amalia (Program Studi Pendidikan Islam Anak Usia Dini, 2025)
This study aims to improve early childhood understanding of sexual education through the use of illustrated story media at KOBER Ar Rahmah. The method used is Classroom Action Research (CAR) based on the Kemmis and McTaggart model, carried out in two cycles. Each cycle consists of planning, action, observation, and reflection stages. The research subjects totaled 28 individuals, including 1 head administrator, 1 assistant teacher, 13 parents, and 13 children aged 2–4 years. Data collection techniques included observation, interviews, documentation, and assessment of children’s learning outcomes. The research findings indicate that illustrated story media effectively enhances children’s understanding of early sexual education aspects, such as recognizing gender differences, identifying private body parts and boundaries (aurat), understanding the concept of safe and unsafe touch, maintaining personal hygiene, and selecting appropriate viewing content. In the pre-observation phase, most children were categorized as Not Yet Emerged. After two implementation cycles, all children showed progress, reaching the Emerged category with an average score of 2.0 or a 100% rate. This media has proven to be effective and enjoyable in increasing young children's understanding of early sexual education. It also enables teachers and parents to introduce sensitive topics in a natural, engaging, and developmentally appropriate manner.